Removal of ammonium and nitrate in recirculating aquaculture systems by the epiphyte Stigeoclonium nanum immobilized in alginate beads - Mohamed Ramli, Norulhuda; Verdegem, M. C. J.; Md Yusoff, Fatimah; Zulkifely, M. K.; Verreth, J. A. J. (Inter Research, 2017)
Incorporation of microalgae in recirculating aquaculture systems (RAS) would absorb the inorganic nitrogen and phosphorus, thus potentially contributing to water purification.Immobilization or entrapment of microalgal cells in spherical gels is a potential method to incor- porate microalgae in the RAS. Filamentous microalgae are presumed to suit the immobilization technique because the gels can serve as substrates for the microalgae to attach. In the first experiment of this study, growth and nitrogen uptake of Stigeoclonium nanum, a filamentous micro-alga, was compared when cultured using an immobilization technique or in a normal suspension.In the second experiment, immobilized S. nanum was cultured in 4 media with different total ammonia nitrogen (TAN) and nitrate-nitrogen (NO3-N) concentrations. The results showed a significantly higher algal growth and TAN removal by S.nanum immobilized in alginate than for S.nanum in free suspension culture. When both TAN and NO3-N were added to the culture medium, the uptake of TAN by immobilized S.nanum was significantly more efficient than NO3-N uptake.Our results indicated that S.nanum was able to grow immobilized in a medium, exhibiting a higher growth and TAN uptake than when the algae were in free suspension. S.nanum preferred ammonium over nitrate, which is suitable for RAS that require removal of the total ammonia which is produced by fish and by organic decomposition in the system.